Pelaksanaan Pelatihan Karyawan di PT Cigwa Indonesia Jaya - Siti Maulidia Apriliani; Palahudin Palahudin (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines the implementation of employee training at PT Cigwa Indonesia Jaya, a company operating in the tourism sector, where training programs have not yet produced optimal results. The main problems identified include the limited competence of instructors and the unequal participation of employees in training activities due to scheduling conflicts with operational working hours. This research aims to analyze the effectiveness of the existing training implementation and identify factors that hinder its optimal application in improving employee performance. The study employs a descriptive quantitative approach, supported by observations and semi-structured interviews. Data were collected through questionnaires distributed to 50 employees who participated in training programs during the 2023–2025 period. The collected data were tested for validity and reliability and analyzed using descriptive statistical techniques. The results indicate that employee training at PT Cigwa Indonesia Jaya has not been fully effective. Most respondents perceived that instructors lacked sufficient pedagogical competence, which affected employees’ understanding of training materials. In addition, the uneven distribution of training participants limited knowledge transfer across departments. These conditions contributed to suboptimal employee performance and inconsistent achievement of company operational targets. The study recommends improving instructor selection, conducting regular training evaluations, and adopting online or blended learning methods to ensure broader employee participation and enhance training effectiveness.